Wallet Key Generation for a Generic Blockchain based on Speech - Rashid, Asmaa; Al-karkhi, Asia Ali Salman; Hassan, Nidaa Flaih (Iraqi Journal of Science, 2023)
As a new technology, blockchain provides the necessary capabilities to assure data integrity and data security through encryption. Mostly, all existing algorithms that provide security rely on the process of discovering a suitable key. Hence, key generation is considered the core of powerful encryption. This paper uses Zernike moment and Mersenne prime numbers to generate strong prime numbers by extracting the features from biometrics (speech). This proposed system sends these unique and strong prime numbers to the RSA algorithm to generate the keys. These keys represent a public address and a private key in a cryptocurrency wallet that is used to encrypt transactions. The benefit of this work is that it provides a high degree of protection to secure personal user transactions by creating secure keys that can be used for insecure channels.